2003
DOI: 10.1086/373963
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Hereditary Nonpolyposis Colorectal Cancer in the United States: High Mutation Detection Rate among Clinically Selected Families and Characterization of an American Founder Genomic Deletion of the MSH2 Gene

Abstract: The identification of germline mutations in families with HNPCC is hampered by genetic heterogeneity and clinical variability. In previous studies, MSH2 and MLH1 mutations were found in approximately two-thirds of the Amsterdam-criteria-positive families and in much lower percentages of the Amsterdam-criteria-negative families. Therefore, a considerable proportion of HNPCC seems not to be accounted for by the major mismatch repair (MMR) genes. Does the latter result from a lack of sensitivity of mutation detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
170
3
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(190 citation statements)
references
References 49 publications
12
170
3
5
Order By: Relevance
“…The sensitivity of germline mutation detection could not be deduced from other studies, as they did not include analysis of hypermethylation of the MLH1 promoter and/or performed less comprehensive germline mutation analyses (Mangold et al, 2005;Barnetson et al, 2006;Niessen et al, 2006). Wagner et al (2003) also found a difference in prevalence of pathogenic MLH1, MSH2, or MSH6 mutations between families that fulfilled the Amsterdam criteria (39 mutations in 49 families (80%)) and those not fulfilling these criteria (five mutations in 10 families (50%)) using methods that detect a similar type of mutations as the methods used in the present study. However, in this study data about the MMR deficiency of the tumours are missing.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of germline mutation detection could not be deduced from other studies, as they did not include analysis of hypermethylation of the MLH1 promoter and/or performed less comprehensive germline mutation analyses (Mangold et al, 2005;Barnetson et al, 2006;Niessen et al, 2006). Wagner et al (2003) also found a difference in prevalence of pathogenic MLH1, MSH2, or MSH6 mutations between families that fulfilled the Amsterdam criteria (39 mutations in 49 families (80%)) and those not fulfilling these criteria (five mutations in 10 families (50%)) using methods that detect a similar type of mutations as the methods used in the present study. However, in this study data about the MMR deficiency of the tumours are missing.…”
Section: Discussionmentioning
confidence: 99%
“…2 A deletion of the first 6 exons of MSH2 has been described previously and leads to a 'classical Lynch syndrome' phenotype. 22 The phenotype of the brother is more severe when compared with classical Lynch syndrome patients because he has multiple synchronous colorectal cancers and also metachronous cancer and more than 10 polyps. Lynch syndrome patients have a slightly increased risk of adenomas (but not more than 10) and have an increased risk of multiple tumours, but mostly two and not more at a time.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a founder mutation in the general US population was not expected; but in fact one such mutation was uncovered very recently, 15,16 namely, a deletion of exons 1 -6 of MSH2. This mutation had remained undiscovered because it was not detectable by standard methods such as sequencing.…”
Section: Common Mutationsmentioning
confidence: 99%